(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The states that compose the sahelian region were born with dire economic, political-administrative and social problems, that contributed to making them a perfect breeding ground for the rise and spread of a wide variety of non-state groups. In particular, terrorism and organized crime generate within power vacuums unprecedented relations, which lead to the perpetuation of violent spirals, that further destabilize the precarious conditions of the Sahel.